Comparisons of Respiratory Pupal Gill Development in Black Flies (Diptera: Simuliidae) Shed Light on the Origin of Dipteran Prothoracic Dorsal Appendages. Issue 2 (19th October 2020) - Yang, Yao Ming; Sun, Qian; Xiu, Jiang-Fan; Yang, Ming
Abstract: During the transformation of immature aquatic dipteran insects to terrestrial adults, the prothoracic pupal respiratory organ enables pupae to cope with flood-drought alternating environments. Despite its obvious importance, the biology of the organ, including its development, is poorly understood. In this study, the developing gills of several Simulium Latreille (Diptera: Simuliidae) spp. were observed using serial histological sections and compared with data on those of other dipteran families published previously. The formation of some enigmatic features that made the Simulium gill unique is detailed. Through comparisons between taxa, we describe a common developmental pattern in which the prothoracic dorsal disc cells not only morph into the protruding respiratory organ, which is partially or entirely covered with a cuticle layer of plastron, but also invaginate to form a multipart internal chamber that in part gives rise to the anterior spiracle of adult flies. The gill disc resembles wing and leg discs and undergoes cell proliferation, axial outgrowth, and cuticle sheath formation. The overall appendage-like characteristics of the dipteran pupal respiratory organ suggest an ancestral form that gave rise to its current forms, which added more dimensions to the ways that arthropods evolved through appendage adaptation. Our observations provide important background from which further studies into the evolution of the respiratory organ across Diptera can be carried out.